Percolation of carriers through low potential channels in thick AlxGa1-xAs (x<0.35) barriers - Kim, DS; Ko, HS; Kim, YM; Rhee, SJ; Hohng, SC; Yee, YH; Kim, WS; Woo, JC; Choi, HJ; Ihm, J; Woo, DH; Kang, KN (AMERICAN PHYSICAL SOC, 1996)
We study by photoluminescence excitation the heretofore unsolved puzzle of a significant charge transfer over a thick (100 to 1500 Angstrom) AlxGa1-xAs barrier in GaAs/AlxGa1-xAs asymmetric double quantum wells, which the normally considered tunneling cannot account for. This phenomenon is completely general, observed in all the samples grown under standard growth conditions (similar to 600 degrees C), that originated from many different sources. The existence of such leakage is also confirmed by time-resolved photoluminescence experiments. However, when the alloy barrier is replaced by an equivalent GaAs/AlAs digital alloy, or by AlAs, the leak largely disappears. In addition, a GaAs barrier separating two shallow InxGa1-xAs quantum wells permits only relatively small transfer. The leak has a weak dependence on the barrier thickness at x=0.3, but is a very strong function of x around x=0.3. We argue that there is no way to explain all of the observed phenomena simultaneously other than by the existence of intrinsic structural inhomogeneities in the alloy. Essentially, there may exist low potential channels in the alloy barrier created by microscopic clustering of like molecules, through which percolationlike transport occurs. This picture is supported by a three-dimensional quantum-mechanical model calculation. Our work pins down the dynamical implications of the partial ordering and clustering in AlxGa1-xAs and related semiconductor ternary alloys. The scope of this paper is exclusively for the transport over thick AlxGa1-xAs barriers (x<0.35) and does not include the relatively small but still non-negligible transport over thick homogeneous barriers such as GaAs, AlAs, and AlAs/GaAs digital alloys, and AlxGa1-xAs (x>0.35). We contend that transport over these thick, homogeneous barriers may be owing to other mechanisms such as dipole-dipole transfer, photon reabsorption, nonequilibrium distribution of carriers, and polariton transport that are also unrelated to conventional tunneling.
Keywords: V-SEMICONDUCTOR ALLOYS; LONG-RANGE-ORDER; QUANTUM-WELL STRUCTURES; MOLECULAR-BEAM EPITAXY; DILUTED MAGNETIC SEMICONDUCTORS; SCANNING-TUNNELING-MICROSCOPY; SHORT-PERIOD SUPERLATTICES; GAAS/ALXGA1-XAS SUPERLATTICES; PHONONS; GROWTH